2000
DOI: 10.1007/s002170000163
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant effectiveness on thermally treated marine lipids by fluorescence detection

Abstract: Previous research has studied fluorescence development during fish processing; as a result, a bathochromic shift towards higher wavelength maxima was detected and employed successfully as a way of measuring quality changes. In the present work, the same fluorescence analysis was tested for assessing the preservative effect of an antioxidant compound on thermally treated marine lipids. For it, two kinds of marine lipids systems (cod liver oil and horse mackerel white muscle) were heated under different time (up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
2
8
1
2
Order By: Relevance
“…The time course of AV during autoxidation of herring oil revealed that the oils were at the secondary oxidation stage. Contrary to reported results (Aubourg 2000;Aidos and others 2001), in this case, the FC was not a useful measure, since no significant changes were detected during storage. The determination of secondary oxidation products as AV measurement is suggested.…”
Section: Oxidative Stabilitycontrasting
confidence: 99%
“…The time course of AV during autoxidation of herring oil revealed that the oils were at the secondary oxidation stage. Contrary to reported results (Aubourg 2000;Aidos and others 2001), in this case, the FC was not a useful measure, since no significant changes were detected during storage. The determination of secondary oxidation products as AV measurement is suggested.…”
Section: Oxidative Stabilitycontrasting
confidence: 99%
“…The antioxidant effect of the different lyophilized quinoa extracts (ANS, AN, CAS, and CA batches) was tested in a model system including a marine oil (cod liver oil, CLO; Merck). CLO is considered an appropriate model system for studying oxidation mechanisms in food containing significant PUFA levels ; previous research has shown its usefulness in order to test the antioxidant behavior of citric acid and jumbo squid ( Dosidicus gigas ) skin extract .…”
Section: Methodsmentioning
confidence: 99%
“…The full-fitted ANOVA models showed that CT and FC were important parameters. In contrast, it was concluded that the CD and tetraenes content were not suitable as quality measurements (data not shown), possibly because of the relatively unstable nature of these latter compounds (Cho and others 1989;Aubourg andothers 1995, 1997). Concerning the measurement of CT, the initial model only showed a significant effect for the storage d of the oils (p < 0.05, power = 0.999).…”
Section: Oxidative Stability Of Extracted Oilmentioning
confidence: 95%
“…The development of tertiary oxidation products (FC) was found to be temperature-independent but decreased as a result of the storage time of the byproducts (p = 0.004, power = 0.930). It is known that oxidation products are unstable and tend to react with biological amino constituents (proteins, peptides, free amino acids) and phospholipids, leading to interaction compounds (Gardner 1979(Gardner , 1987Pokorny 1987) that can be assessed by their fluorescent properties (Aubourg and Medina 1997;Aubourg andothers 1997, 1998). Evidence has demonstrated that fluorescent substances formed from oxidized membrane lipids remain attached to the amino constituents (Lio and Yoden 1988;Hasegawa and others 1992).…”
Section: Quality Of the Extracted Oilmentioning
confidence: 98%
See 1 more Smart Citation